Whole-genome analysis and description of an outbreak due to carbapenem-resistant Ochrobactrum anthropi causing pseudo-bacteraemias. (November 2018) - Montaña, S.; Fernandez, J.S.; Barenboim, M.; Hernandez, M.; Kayriyama, C.; Carulla, M.; Iriarte, A.; Ramirez, M.S.; Almuzara, M.
Abstract: Ochrobactrum anthropi, a rare human pathogen, has been isolated predominantly from patients with catheter-related bacteraemia and rarely from other infections. In 2016, six cases of pseudo-bacteraemia caused by carbapenem-resistant O. anthropi isolates were recovered from an Argentinian hospital. The resistant phenotype exposed by the isolates caught our attention and led to an extensive epidemiologic investigation. Here we describe the characterization of a carbapenem-resistant O. anthropi outbreak whose probable cause was by contaminated collection tubes. The genome analysis of one strain revealed the presence of various resistant determinants. Among them, a metal-dependent hydrolase of the β-lactamase superfamily I, phnP, was found. Lately the recovery of unusual multidrug-resistant pathogens in the clinical setting has increased, thus emphasizing the need to implement standardized infection control practice and epidemiologic investigation to identify the real cause of hospital outbreaks.